Incidence and Risk Factors for Residual High-Grade Pivot Shift After ACL Reconstruction With or Without a Lateral Extra-articular Tenodesis. Issue 5 (7th May 2021) - Jacquet, Christophe; Pioger, Charles; Seil, Romain; Khakha, Raghbir; Parratte, Sebastien; Steltzlen, Camille; Argenson, Jean-Noel; Pujol, Nicolas; Ollivier, Matthieu
Background: Residual rotatory knee laxity at midterm follow-up after isolated anterior cruciate ligament reconstruction (ACLR) versus ACLR with lateral extra-articular tenodesis (LET) remains an issue. Purpose/Hypothesis: To evaluate the outcomes of ACLR with or without additional LET at a minimum 2-year follow-up in patients with preoperative high-grade pivot shift (PS). Our hypothesis was that the addition of LET would decrease the risk of secondary meniscal injury and the presence of residual high-grade PS at follow-up. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective analysis performed at 3 sports medicine centers identified 266 study patients; all had a high-grade PS (grade 2 or 3) preoperatively and underwent isolated ACLR with or without LET. Four different ACLR techniques were used: single-strand quadrupled semitendinosus (ST4) ACLR without LET (ST4 group; n = 55), ST4 with anatomic LET (ST4+LET group; n = 77), bone–patellar tendon and modified Lemaire LET (BTB+LET group; n = 43), and quadriceps tendon and modified Lemaire LET (QT+LET group; n = 91). At follow-up, we evaluated for the presence of high-grade (grade ≥2) PS. Preoperative meniscal tears and their treatment were recorded. Results: Overall, 185 (69.5%) patients had at least 1 meniscal tear at index surgery. The mean follow-up period was 44.3 months; 47 (17.7%) patients had a new meniscal tear and 64 (24%) patients had a high-grade PS at follow-up. Compared with meniscal repair, significant predictors for high-grade PS at follow-up were meniscectomy (odds ratio [OR] = 2.65 [95% CI, 1.19-5.63]; P = .02) and nonrepair of preoperative meniscal tear (OR = 3.26 [95% CI, 1.27-9.43]; P = .007). The appearance of a new symptomatic meniscal tear was the strongest significant predictor of high-grade PS at follow-up (OR = 4.31 [95% CI, 2.31-8.06]; P < .001). No significant correlation was observed between the addition of LET and the presence of high-grade PS at follow-up. Conclusion: In the current study, 1 in 4 patients with high-grade PS before ACLR with or without LET was at risk of residual rotatory knee laxity at mean 44-month follow-up, regardless of the technique used. Repairing a pre-existing meniscal lesion was more effective than performing LET to decrease the presence of a high-grade PS at follow-up.